Komplikationsmanagement nach Lebertransplantation - Houben, Philipp; Gotthardt, Daniel; Radeleff, Boris; Sauer, Peter; Büchler, Markus W.; Schemmer, Peter (Der Chirurg, 2015)
The interdisciplinary management of postoperative complications in liver transplantation is of extreme importance. Due to organ shortage and prioritization of the most severely ill recipients in the model for end-stage liver disease (MELD)-based allocation, both donor and recipient associated morbidity are increasing. An interdisciplinary, structured monitoring concept is essential for the timely identification and specific treatment of postoperative complications. Interdisciplinary clinical rounds, laboratory testing and Doppler ultrasound monitoring of the graft perfusion are as important as comprehensive anti-infection prophylaxis and immunosuppression. Arterial perfusion disorders of any kind, biliary complications and postoperative fluid accumulation demand individualized therapeutic concepts. In summary, the success of liver transplantation depends on the communication and coordinated interdisciplinary cooperation of all disciplines involved.